2001
DOI: 10.1037/0022-3514.80.5.706
|View full text |Cite
|
Sign up to set email alerts
|

Achievement goals and optimal motivation: Testing multiple goal models.

Abstract: Currently, there is a debate about which types of achievement goals promote optimal motivation. A number of theorists argue for a mastery goal perspective focusing on the adaptive consequences of mastery goals and the maladaptive consequences of performance goals. Others endorse a multiple goal perspective in which both mastery and performance goals can be beneficial. The purpose of the present investigation was to review why this debate has emerged and to offer a critical test of the mastery versus multiple g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
555
8
37

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 650 publications
(649 citation statements)
references
References 54 publications
40
555
8
37
Order By: Relevance
“…12-14 The approach-avoidance achievement goal orientation is predictive of achievement. [8][9][10][11]15,16 Mastery goals were found to be positive predictors of depth of study, effort, and persistence. Performance goals were positive predictors of cursory or surface study, effort, and persistence, and performance avoidance was found to be a positive predictor of disorganized studying.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…12-14 The approach-avoidance achievement goal orientation is predictive of achievement. [8][9][10][11]15,16 Mastery goals were found to be positive predictors of depth of study, effort, and persistence. Performance goals were positive predictors of cursory or surface study, effort, and persistence, and performance avoidance was found to be a positive predictor of disorganized studying.…”
Section: Introductionmentioning
confidence: 89%
“…These reasons or motivations are important determinants of an individual's achievement goal orientation. [7][8][9][10][11] Achievement goal orientation theory suggests there are 2 broad thought processes and behaviors used to achieve competence in either assigned or self-directed learning goals (performance and mastery). Performance goal orientation is dominated by those who seek to gain competence by performing as well as possible relative to others.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to examining whether these individuals are more likely to adopt performance-avoidance goals, a secondary question was whether they are less likely to adopt performance-approach or mastery goals (Barron & Harackiewicz, 2001). We also compared the patterns of spontaneous goal adoption of higher achievementoriented and lower achievement-oriented women.…”
Section: Studymentioning
confidence: 99%
“…Several researchers expounded the positive view of performance goals (Barron & Harackiewicz, 2001;Harackiewicz, Barron, Pintrich, Elliot, & Thrash, 2002;Koopman et al, 2014;Pintrich et al, 2003;Wolters, 2004). The positive views of performance goals were explained by the revised goal theory that performance-oriented goals may be helpful for increasing students' cognitive learning (Harackiewicz et al, 2002).…”
Section: Performance Goals and Learning Strategiesmentioning
confidence: 99%